Trend Infeksi Penyakit Menular Seksual dan Sifilis di Provinsi Nusa Tenggara Barat: Perspektif Global Health Security - Muhammad Freddy Candra Sitepu; Astri Ferdiana; Lalu Hamzi Fikri; I Kadek Mulyawan; Rifana Cholidah; Anom Josafat; Nila Febriana (Malahayati Nursing Journal, 2026)
ABSTRACT Sexually transmitted diseases (STDs) and syphilis remain major global public health challenges. Syphilis, caused by Treponema pallidum, has shown a concerning resurgence in recent years. No study has described the profile of STDs, particularly syphilis, in West Nusa Tenggara. To describe the profile of STDs and syphilis in West Nusa Tenggara Province. A retrospective descriptive study using surveillance data of infectious diseases reported by all public health centers (Puskesmas) in 2024. Data were grouped by district and key-risk population. Analysis used SPSS version 25 and presented in tables and charts. A total of 957 STD cases were reported. The highest proportions were found in Mataram (45.9%) and Sumbawa (34.3%). The largest affected group was pregnant women (28.8%), followed by men who have sex with men (15.3%), prospective marriage partners (10.9%), multiple partners (10.4%), sex worker clients (9.5%), co-infections (8.5%), general population (7.9%), and female sex workers (6.9%). Among these, 475 cases were syphilis, predominantly in Sumbawa (69.1%), with pregnant women accounting for 53.9%. Conclusion: Syphilis is the most common STD in West Nusa Tenggara. The burden is highest in Sumbawa and among pregnant women. This finding highlights the urgency of strengthening prevention and screening programs. Keywords: STD, Syphilis, Surveillance, Global Health Security. ABSTRAK Penyakit menular seksual (PMS) dan sifilis masih menjadi tantangan kesehatan masyarakat global. Sifilis yang disebabkan oleh Treponema pallidum menunjukkan peningkatan kasus dalam beberapa tahun terakhir. Di Provinsi Nusa Tenggara Barat belum terdapat penelitian yang menggambarkan profil PMS, khususnya sifilis. Mendeskripsikan profil PMS dan sifilis di Provinsi Nusa Tenggara Barat. Penelitian deskriptif retrospektif menggunakan data surveilans penyakit menular dari seluruh Puskesmas tahun 2024. Data dianalisis berdasarkan wilayah kabupaten/kota dan kelompok populasi berisiko. Analisis dilakukan secara deskriptif menggunakan SPSS versi 25 dan disajikan dalam tabel dan grafik. Terdapat 957 kasus PMS. Proporsi tertinggi ditemukan di Kota Mataram (45,9%) dan Kabupaten Sumbawa (34,3%). Kelompok terbanyak adalah ibu hamil (28,8%), diikuti laki-laki seks dengan laki-laki (15,3%), calon pengantin (10,9%), pasangan seksual multipel (10,4%), pelanggan pekerja seks (9,5%), koinfeksi PMS lain (8,5%), populasi umum (7,9%), dan pekerja seks perempuan (6,9%). Dari seluruh kasus, 475 merupakan sifilis dan dominan di Sumbawa (69,1%), dengan 53,9% terjadi pada ibu hamil. Sifilis merupakan PMS terbanyak di NTB, dengan beban tertinggi di Kabupaten Sumbawa dan pada ibu hamil. Diperlukan upaya pencegahan dan skrining yang lebih intensif. Kata Kunci: PMS, Sifilis, Surveilans, GHS.